Surgery for cholangiocarcinoma. (20th May 2019) - Cillo, Umberto; Fondevila, Constantino; Donadon, Matteo; Gringeri, Enrico; Mocchegiani, Federico; Schlitt, Hans J.; Ijzermans, Jan N. M.; Vivarelli, Marco; Zieniewicz, Krzysztof; Olde Damink, Steven W. M.; Groot Koerkamp, Bas
Abstract: Surgical resection is the only potentially curative treatment for patients with cholangiocarcinoma. For both perihilar cholangiocarcinoma (pCCA) and intrahepatic cholangiocarcinoma (iCCA), 5‐year overall survival of about 30% has been reported in large series. This review addresses several challenges in surgical management of cholangiocarcinoma. The first challenge is diagnosis: a biopsy is typically avoided because of the risk of seeding metastases and the low yield of a brush of the bile duct. However, about 15% of patients with suspected pCCA are found to have a benign diagnosis after resection. The second challenge is staging; even with the best preoperative imaging, a substantial percentage of patients has occult metastatic disease detected at staging laparoscopy or early recurrence after resection. The third challenge is an adequate volume and function of the future liver remnant, which may require preoperative biliary drainage and portal vein embolization. The fourth challenge is a complete resection: a positive bile duct margin is not uncommon because the microscopic biliary extent of disease may be more extensive than perceived on imaging. The fifth challenge is the high post‐operative mortality that has decreased in very high volume Asian centres, but remains about 10% in many Western referral centres. The sixth challenge is that even after a complete resection most patients develop recurrent disease. Recent randomized controlled trials found conflicting results regarding the benefit of adjuvant chemotherapy. The final challenge is to determine which patients with cholangiocarcinoma should undergo liver transplantation rather than resection.